PENGARUH PENGGUNAAN PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN SENI RUPA DI SMP NEGERI 2 PADANG - Rini Nofita, Drs. Yusron Wikarya, M.Pd. Yofita sandra, S.Pd., M.Pd. (Serupa The Journal of Art Education, 2017)
This research was aimed to determinethe effect of using a scientific approach to the learning outcomes of students in fine arts at SMP Negeri 2 Padang. This type of research is quasi-experimental with pretest-posttest control group design. The results showed that the class is taught by scientific approach to the learning outcomes different from whom were though by who are taught the conventional approach in SMP Negeri 2 Padang. Based on the hypothesis test carried out that the value of tvalue= 2,242 and ttable = 1,669 at the level of alpha = 0,05. This means that tvalue> ttable. It was concluded that the use of the scientific approach has positive influence on improving student learning outcomes in learning art in SMP Negeri 2 Padang.Kata kunci : Scientific Approaches, and Student Learning Outcomes